Chemical variability in wakabayashilite: a real feature or an analytical artifact?. (June 2014) - Bindi, L.; Bonazzi, P.; Zoppi, M.; Spry, P. G.
Abstract: Wakabayashilite is a rare mineral with ideal formula [(As, Sb)6 S9 ][As4 S5 ]. Its structure consists of an [M6 S9 ] bundle-like unit (M = As, Sb) running along the [001] axis and [As4 S5 ] cage-like molecules. In this study, samples of wakabayashilite from different occurrences (Khaidarkan, Kyrgyzstan; Jas Roux, France; White Caps mine, USA; Nishinomaki mine, Japan) were selected to verify the possible presence of different molecular groups replacing the As4 S5 molecule. Given the chemical (electron probe microanalysis-wavelength dispersive spectroscopy), spectroscopic (micro-Raman) and structural (single-crystal X-ray diffraction) results obtained, it appears evident that only the As4 S5 molecular group is present in the wakabayashilite structure and that the apparent non-stoichiometry reported in literature is actually due to unreliable chemical analyses. The structural role of the minor elements (Cu, Zn and Tl) in wakabayashilite is also discussed.